Pengaruh Pengendalian Internal, Komitmen Organisasi dan Budaya Organisasi Terhadap Kecurangan Akuntansi - Ni Putu Septia Purnama Putri; Ni Komang Sumadi; Putu Cita Ayu (UNHI Press, 2025)
Accounting fraud isaction taken by irresponsible parties in order to gain profit by carrying out dishonest and unethical practices within the scope of accounting. The goal of studie was fordetermine some efect internal controling, organizational commitment aand organizational culture’ on accounting fraud at BUMDesa in Sidemen Sub-district. The resarch was conduted by taking locations BUMDesa at Sidemen District. This is quantitatif research. Population was 67 employee of BUMDesa who were still operating in Sidemen District. Sampling techniquue used a purposive samapling methode, the sampel is 33 person from BUMDesa which is chairman, secretary, treasurer, analyst, and head of BUMDesa business unit. Data obtained from give questionnaires to the employee as a responden. Data analyisis techniique is Multipel Liniar Regresion Analyisis with teh regression equation Y = 57.619 - 0.316X1 - 1.144X2 - 0.133X3 + e. Result of study showing internal controling does not give effect to performancse BUMDesa employes. and then the internal controlling also has no effect for acounting fraud, as evidenced by teh value of titung = -1.456 with significants value which is 0.156>0.05. Organizational commitment has significance negative efect on accounting fraud, as evidenced by the tcunt value = -2.830 with significant 0.008 <0.05. Organisational culture there’s no effect at acounting fraud, as evidenced by the value of thitung = -0.551 with significant 0.586>0.05.